Improving Learning Outcomes by Using Puzzle Media in Islamic Religious Education Subjects - Iriani, Nur; Çoruh, Hakan (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: The aim of this research is to find out whether there has been an increase in student motivation and learning outcomes in Islamic Religious Education subjects using puzzle media. Methodology:This type of research is classroom action research, so this research has activity stages in the form of cycles. Kemmis and Mc Taggart's classroom action research model, which in one cycle consists of four components. Data collection techniques in this research are tests, observations and interviews. The stages of data analysis carried out in this research are reducing data and presenting data. Main Findings: The results of this research began with giving an initial test to 17 students, 13 students completed it and 4 students completed it individually with a learning completion percentage of 23.00%. Furthermore, in cycle I, out of 17 students, 9 students did not complete and 8 students completed individually with a completion percentage of 47.1%. Meanwhile, in cycle II, out of 17 students, 14 students had completed their studies with a percentage of 82.3%, and 3 students, 17.7%, had not completed their studies. Novelty/Originality of this study: As input for prospective teacher students on how to motivate students to learn and it is hoped that the results of this research will later become material for study in the use of media in the learning process.